Two-Year clinical outcomes after coronary bifurcation stenting in older patients from Korea and Italy - Kim, Ju Hyeon; Franchin, Luca; Hong, Soon Jun; Cha, Jung-Joon; Lim, Subin; Joo, Hyung Joon; Park, Jae Hyoung; Yu, Cheol Woong; Lim, Do-Sun; De Filippo, Ovidio; Gwon, Hyeon-Cheol; Piroli, Francesco; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Older patients who treated by percutaneous coronary intervention (PCI) are at a higher risk of adverse cardiac outcomes. We sought to investigate the clinical impact of bifurcation PCI in older patients from Korea and Italy. Methods We selected 5,537 patients who underwent bifurcation PCI from the BIFURCAT (comBined Insights from the Unified RAIN and COBIS bifurcAtion regisTries) database. The primary outcome was a composite of target vessel myocardial infarction, clinically driven target lesion revascularization, and stent thrombosis at two years. Results In patients aged ≥75 years, the mean age was 80.1 ± 4.0 years, 65.2% were men, and 33.7% had diabetes. Older patients more frequently presented with chronic kidney disease (CKD), severe coronary calcification, and left main coronary artery disease (LMCA). During a median follow-up of 2.1 years, older patients showed similar adverse clinical outcomes compared to younger patients (the primary outcome, 5.7% vs. 4.5%; p = 0.21). Advanced age was not an independent predictor of the primary outcome (p = 0.93) in overall patients. Both CKD and LMCA were independent predictors regardless of age group. Conclusions Older patients (≥75 years) showed similar clinical outcomes to those of younger patients after bifurcation PCI. Advanced age alone should not deter physicians from performing complex PCIs for bifurcation disease.